Transitions between informal and formal employment: results from a worker survey in Bangladesh - Gutierrez, Italo A.; Kumar, Krishna B.; Mahmud, Minhaj; Munshi, Farzana; Nataraj, Shanthi (© 2017 RAND Corporation, 2017)
This article was published in RAND Labor and Population [© 2017 RAND Corporation] and the definite version is available at: https://www.rand.org/pubs/working_papers/WR1199.html